2002
DOI: 10.1002/j.0022-0337.2002.66.12.tb03609.x
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences in Career and Practice Patterns of PGD‐Trained Dentists

Abstract: This study compares differences by gender in the practice patterns and professional activities of general dentists, specialists, and dentists with Advanced Education in General Dentistry (AEGD) or General Practice Residency (GPR) training. The UCLA School of Dentistry surveyed a random sample of 6,725 dentists graduating from dental school in 1989, 1993, and 1997 as part of an evaluation of the impact of federal funding on postgraduate general dentist (PGD) programs. The survey asked about current practice, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
23
2

Year Published

2002
2002
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 9 publications
2
23
2
Order By: Relevance
“…A study of Australian dentists found higher rates of caries prevention used by female dentists (14). However, Atchison (42) did not find gender differences in services grouped into a single category of ‘sealants/fluoride varnish/topical varnishes’, which would be similar to combining our two questions – dental sealants and in‐office fluoride. Brennan and Spencer (14) also found that younger dentists were the most frequent users of fluoride.…”
Section: Discussionsupporting
confidence: 54%
“…A study of Australian dentists found higher rates of caries prevention used by female dentists (14). However, Atchison (42) did not find gender differences in services grouped into a single category of ‘sealants/fluoride varnish/topical varnishes’, which would be similar to combining our two questions – dental sealants and in‐office fluoride. Brennan and Spencer (14) also found that younger dentists were the most frequent users of fluoride.…”
Section: Discussionsupporting
confidence: 54%
“…In spite of the high inflow of females into the dentistry workforce, female dentists remain the minority among dental academics and leaders. Men with postgraduate qualifications hold most senior management positions, while women are more likely to be employed in faculty or government positions [14] [17]. Overall, the professionalization of dental practice has resulted in the continuation and consolidation of male dominance among specialists; studies highlight the fact that males still far outnumber females in terms of specialization in various fields [1] [18].…”
Section: Academia and Leadershipmentioning
confidence: 99%
“…The influx of women into dentistry and their roles in dental academics have been a topic of interest for many years. One recent study examined the gender differences in career and practice patterns of postgraduate general dentistry (PGD) trained dentists 9 . They showed female PGD‐trained dentists tend to choose career paths in government, hospital care, or dental education rather than private practice 9 .…”
mentioning
confidence: 99%
“…One recent study examined the gender differences in career and practice patterns of postgraduate general dentistry (PGD) trained dentists 9 . They showed female PGD‐trained dentists tend to choose career paths in government, hospital care, or dental education rather than private practice 9 . In addition, women were more likely to pursue a career in academics 10 .…”
mentioning
confidence: 99%